Characteristics of Modified Kimpul (Xanthosoma Sagittifolium) and Mocaf Flour Bread With Potato (Solanum tuberosum L) Sourdough Starter - Ika Dyah Kumalasari; Riantika Aulia Putri; Endah Sulistiawati; Gita Indah Budiarti (Universitas Darussalam Gontor, 2023)
The fiber content in flour can be increased using a physical modification method (Autoclaving-cooling). Processed food products are favored by the public to apply it to bread with the use of natural yeast (sourdough) derived from potatoes because it is high in carbohydrates and low in calories. The purpose of this study was to determine characteristics of modified kimpul (Xanthosoma sagittifolium) and mocaf flour bread with potato (Solanum tuberosum L) sourdough starter. This study was conducted using a completely randomized design (CRD) with one factor, namely the ratio of wheat flour: modified kimpul tuber: mocaf of F0 (100%T:0%K:0%M) (control); F1 (20%T:50%K:30%M); F2 (20%T:40%K:40%M); and F3 (20%T:30%K:50%M) using potato sourdough starter. Parameters analyzed were total sugar, texture (chewiness),and organoleptic test(taste, aftertaste, color, aroma, texture, and overall preference). Data collection was carried out by 25 untrained panelists. Statistical analysis of data used the One Way Analysis Of Variance (ANOVA) test with a significance level of 5%, followed by Duncan's test and percentage descriptive analysis. The results of the analysis of the total sugar test and texture (chewiness)on bread showed a significant difference and sample F1 (20%T: 50%K: 30%M) decreased the total sugar content.The results of organoleptic test showed a significant difference and the acceptability of each parameter of taste, aftertaste, color, texture, and overall preference was 70,5% according to the criteria for liking, but the aroma parameter did not show a significant difference.